2015
DOI: 10.3348/kjr.2015.16.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Surveillance of Patients with Breast Cancer after Primary Treatment: Current Recommendations

Abstract: Women who have been treated for breast cancer are at risk for second breast cancers, such as ipsilateral recurrence or contralateral metachronous breast cancer. As the number of breast cancer survivors increases, interest in patient management and surveillance after treatment has also increased. However, post-treatment surveillance programs for patients with breast cancer have not been firmly established. In this review, we focus on the imaging modalities that have been used in post-treatment surveillance for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 60 publications
1
43
0
3
Order By: Relevance
“…MRI also demonstrated comparable sensitivity (75%–100%) and specificity (66.6%–93%) with acceptable accuracy (95%) [10]. These studies suggest a potential role of supplemental imaging tests in survivors of breast cancer.…”
Section: Introductionmentioning
confidence: 97%
“…MRI also demonstrated comparable sensitivity (75%–100%) and specificity (66.6%–93%) with acceptable accuracy (95%) [10]. These studies suggest a potential role of supplemental imaging tests in survivors of breast cancer.…”
Section: Introductionmentioning
confidence: 97%
“…Dynamic contrast-enhanced (DCE) MRI is an integral part of the proposed standard protocol Imagingfor breast cancer diagnosis, which provides important information about temporal and spatial uptake of the contrast medium (56). Recently, research focused on diffusion-weighted imaging, proton spectroscopy, and perfusion MRI, has suggested that these techniques may offer potential improvements for diagnostic breast imaging (789101112). …”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that early detection of recurrence in asymptomatic patients during posttreatment follow‐up has potential benefits . However, posttreatment surveillance programs for patients with breast cancer have not yet been firmly established . A regular history, physical examination, and mammography are usually recommended for breast cancer follow‐up …”
mentioning
confidence: 99%
“…Ultrasonography (US) is a useful surveillance imaging method for the breast, axillary areas, and chest wall in women who have received breast cancer treatment . Ultrasonography can show ipsilateral recurrent or contralateral metachronous breast cancers with higher sensitivity (91%–97%) than palpation or mammography, which have achieved sensitivity values of 45.5% to 79.0% and 45.0% to 87.0%, respectively . However, a higher cancer detection yield is associated with an increased rate of false‐positive findings…”
mentioning
confidence: 99%
See 1 more Smart Citation